701 Combined Endovascular and Percutaneous Treatment of Traumatic Pseudoaneurysm of Profunda Femoris Artery: A Case Report. (4th May 2021) - Malik, P; Makar, R; Joshi, S; Balakrishnan, A
Abstract: Pseudoaneurysms of the profunda femoris artery are rare complications of femoral fractures, seen especially after orthopaedic interventions for the same. We present a case of an 89-year-old Caucasian male with a left neck of femur fracture, repaired with a dynamic hip screw. He presented to us a month later with a painful swollen thigh and deep vein thrombosis. The patient underwent arterial duplex and CT angiogram scans and was found to have a pseudoaneurysm in his left profunda femoris artery, measuring 3x3x4.5cm. This was treated with balloon angioplasty and stenting. However, his stent surveillance duplex scan, a month later, showed that the pseudoaneurysm was largely thrombosed with a patent core that was being fed by a communicating vessel from the superficial femoral artery. A subsequent angiogram showed no obvious feeding vessel. The patent pseudoaneurysm was then treated by percutaneous injection of thrombin. Exclusion of the pseudoaneurysm was confirmed by a follow-up duplex scan. It is essential to treat all feeding vessels of pseudoaneurysms in the presence of a rich collateral supply. Profunda femoris false aneurysms can thus be treated entirely by endovascular/percutaneous methods and so, potentially avoid open surgery.